UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA DAN PROFESIONAL GURU DI MADRASAH ALIYAH NEGERI PURBALINGGA - Anwar Fauzi; Muh.Hanif (STKIP Subang, 2024)
A good principal is a principal who pays attention to the development of his teachers, including teacher professionalism. Leadership functions are: determining goals, explaining, implementing, choosing the right method, providing and stimulating members to work. Based on observations made by the author at MAN Purbalingga, the school's management of the educational institution carried out by the principal is very good. The principal is responsible for the progress of education in the school. The school principal makes various efforts to improve the performance and professionalism of teachers, so that they can achieve the vision, mission and goals of the school. The type of research that the researcher conducted used qualitative research with a qualitative descriptive approach. Data collection through observation, interviews and documentation. The object of this research is the school principal's efforts to improve teacher performance and professionalism. Research subjects are people from whom information sources can be taken. The subject of this research is the Principal of the Purbalingga State Madrasah Aliyah School.